Mini-Invasive Robot-Assisted Surgery of the Brachial Plexus: A Case of Intraneural Perineurioma - Lequint, Thierry; Naito, Kiyohito; Chaigne, Dominique; Facca, Sybille; Liverneaux, Philippe (Journal of Reconstructive Microsurgery, 2012)
Brachial plexus surgery requires extensive incisions. They are esthetically unsightly and compromise the quality of recovery after nerve repair surgery. We present a new approach to brachial plexus surgery using mini-invasive robot-assisted surgery to perform a biopsy of an intraneural perineurioma of the right brachial plexus in a 12-year-old girl.
Keywords: brachial plexus; Da Vinci robot; microsurgery; nerve; perineurioma; tumor; robot; telemicrosurgery